The λ Mechanism of the 0νββ-Decay - Šimkovic, Fedor; Štefánik, Dušan; Dvornický, Rastislav (Frontiers in Physics, 2017)
The λ mechanism (WL − WR exchange) of the neutrinoless double beta decay (0νββ-decay), which has origin in left-right symmetric model with right-handed gauge boson at TeV scale, is investigated. The revisited formalism of the 0νββ-decay, which includes higher order terms of nucleon current, is exploited. The corresponding nuclear matrix elements are calculated within quasiparticle random phase approximation with partial restoration of the isospin symmetry for nuclei of experimental interest. A possibility to distinguish between the conventional light neutrino mass (WL − WL exchange) and λ mechanisms by observation of the 0νββ-decay in several nuclei is discussed. A qualitative comparison of effective lepton number violating couplings associated with these two mechanisms is performed. By making viable assumption about the seesaw type mixing of light and heavy neutrinos with the value of Dirac mass mD within the range 1 MeV < mD < 1 GeV, it is concluded that there is a dominance of the conventional light neutrino mass mechanism in the decay rate.